Extraction of eco-friendly and biodegradable surfactant for inhibition of copper corrosion during acid pickling - Mervette Elbatouti; Howida A Fetouh (Adsorption Science & Technology)
A novel, cheap, less toxic, and easier-prepared gelatin surfactant is successfully used as corrosion inhibitor for the corrosion of copper in 0.1 M H 2 SO 4 at the temperature range: 25–55°C. The critical micelle concentration of the surfactant was determined from surface tension measurements. The inhibition efficiency was determined from potentiodynamic polarization and electrochemical impedance spectroscopy techniques. For surfactant acted by adsorption at copper/solution interface, an inhibition efficiency up to 68 was obtained at critical micelle concentration (70 ppm) of surfactant at 35°C. The free energy of adsorption was calculated and discussed. The surface parameters of gelatin surfactant were calculated and correlated to the inhibition efficiency. They were also calculated from its surface tension profile including: critical micelle concentration), maximum surface excess (Γ max ), and minimum surface area (A min ). The thermodynamic of micellization, free energies of micellization (ΔG mic ) and entropy of micellization, was calculated and discussed. The formation of compact and adherent monomolecular adsorbed film on copper substrate was confirmed.